2000
DOI: 10.1073/pnas.210244497
|View full text |Cite
|
Sign up to set email alerts
|

A structural basis for drug-induced long QT syndrome

Abstract: L ong QT syndrome (LQT) is an abnormality of cardiac muscle repolarization that predisposes affected individuals to a ventricular arrhythmia that can degenerate into ventricular fibrillation and cause sudden death (1). The cellular mechanism of the lengthened QT interval recorded on the body surface electrocardiogram is prolonged ventricular action potentials. Recent genetic discoveries have determined that the molecular mechanism of inherited LQT is mutations in one of several genes [e.g., HERG (2), KCNE2 (3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
544
2
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 864 publications
(581 citation statements)
references
References 33 publications
34
544
2
1
Order By: Relevance
“…The binding site for structurally diverse blockers was previously localized to specific residues in S6 and the base of the pore helix that face toward the central cavity (29). F656 and Y652 in S6 are the most important residues for binding of blockers.…”
Section: Discussionmentioning
confidence: 99%
“…The binding site for structurally diverse blockers was previously localized to specific residues in S6 and the base of the pore helix that face toward the central cavity (29). F656 and Y652 in S6 are the most important residues for binding of blockers.…”
Section: Discussionmentioning
confidence: 99%
“…In our experiments we were guided by more recent insights into the structure of the methanesulfonanilide binding site of HERG K ϩ channels (19,20). We used the known structure-activity relationship of the noncardiac drug astemizole to compare the relative efficacies of channel block and channel rescue.…”
Section: Mutations In the Human Ether-a-gogo-related Gene (Herg) Kmentioning
confidence: 99%
“…These blockers appear to interact with different portions of the extended binding site for methanesulfonanilides in the inner vestibule of HERG (19). We used E4031, a methanesulfonanilide drug in which the methanesulfonyl group is thought to bind to a pocket formed between the pore helix and the S6 helix and its aromatic piperidine ring to aromatic amino acid residues at Tyr-652 and Phe-656.…”
Section: Restoration Of Herg G601s Trafficking By Incubation Withmentioning
confidence: 99%
“…PCR products were purified after de novo mutation in the principal heart sodium channel (SCN5A) and a common polymorphism in KCNH2 that codes for hERG, a critical heart potassium channel known to contribute to most cases of drug-induced LQTS (Mitcheson et al, 2000). In a first study, we had characterized the biophysical properties of the mutant sodium channels alone expressed in HEK293 cells and found that the mutation resulted in defects in inactivation consistent with the LQT phenotype observed in the proband (Bankston et al, 2007b).…”
Section: Genomic Sequencingmentioning
confidence: 99%